La desintegración familiar y su relación con el rendimiento académico en el área de ciencias naturales de las y los estudiantes de quinto, sexto y séptimo grados del subnivel básica media de educación general básica, de la escuela de educación básica “IV Centenario nº 1” de la ciudad de Loja. Año lectivo 2012-2013 - Reyes Abad, Isabel Maritza (2014)
This research work, entitled: Family breakdown and its relation to academic performance in the area of natural sciences and students of the fifth, sixth and seventh grades of elementary and secondary basic education sub-level school education Basic "IV Centenario N º 1", from the city of Loja. 2012-2013 school year. In which it has been proposed as a general objective: to determine the relationship in family disintegration and the various factors that influence academic performance and students in fifth, sixth and seventh grades of General Basic Education School of Basic Education "IV Centenario No. 1" of the city of Loja. This is a qualitative study, descriptive, which were used the Scientific Method, the Descriptive Method Analytical Method Synthetic and Theoretical Method - Deductive. Techniques such as structured interviews and the survey, together with their instruments, structured interview guide and the questionnaire allowed data collection in the field research. The research universe consisted of a director, eight professors, 147 students and 143 parents in total, 299 individuals. After the analysis and interpretation of the results, it was concluded that the directors of the institution does not carry out a detailed and systematic registration of girls and children with problems of family breakdown, which is not allowing the timely intervention of specialized personnel, somehow shoveling situation, likewise other conclusion is that the parents of the students do not cooperate with the authorities of the school, and who do not attend when they call them, nor help the development of their child's homework, it is charge his brothers and other relatives. In this context, it is recommended to the directors of the institution, take a systematic and detailed file that allows the quick and timely intervention specialist to contribute to solving the problems staff, as well as the establishment of interagency agreements by of managers, with the Ministry for Economic and Social Inclusion, for example, to provide regular human talent involved in the updating of teachers, in the same way, teachers are encouraged to establish and implement the School for parents, in which multiple activities to strengthen integration and peaceful coexistence of families therefore could be obtained as a final conclusion that family breakdown is a social problem that affects well children because that institution develop separation of parents directly affects their school performance and that this upsets their emotional and social stability.